SELF-DIRECTED AND INDEPENDENT LEARNING IN HIGHER EDUCATION: CRITICAL DISCOURSE ANALYSIS - Teresevičienė, Margarita; Kaminskienė, Lina; Žydžiūnaitė, Vilma; Gedvilienė, Genutė (Acta Paedagogica Vilnensia, 2012)
The authors tryes to clarify the concepts of independent and self-directed learning by finding their relations, differences and similarities in the context of higher education institutions. While discussing these two concepts, their main characterising features and elements are identified (motives, abilities, situations, contexts, etc.). The authors argue whether these features and elements allow identifying independent and self-directed learning as synonyms and using them in parallel, or there still exist some significant differences which enable talking about different aspects of these phenomena.Critically evaluating the described concepts of independent and self-directed learning in the research works of Lithuanian and foreign researchers, as well as taking into consideration the variety of available quantitative and qualitative studies, the authors investigate important factors in higher education, which should help teachers and students to develop their independent and self-directed learning skills. The authors try to indentify the didactic approaches and learning strategies (including teachers’ role) that are most effective in higher education as promoting independent and self-directed learning.
Keywords: independent learning; self-directed learning; autonomous learning